1995
DOI: 10.1038/ng1295-428
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations of the BRCA1 gene in breast and ovarian cancer families provide evidence for a genotype–phenotype correlation

Abstract: Mutations in the BRCA1 gene, discovered in 1994, are associated with an 80-90% lifetime risk of breast cancer. We have analysed 60 families with a history of breast and/or ovarian cancer for germline mutations in BRCA1. Twenty-two different mutations were detected in 32 families (53%), of which 14 are previously unreported. We observed a significant correlation between the location of the mutation in the gene and the ratio of breast to ovarian cancer incidence within each family. Our data suggest a transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
238
1
7

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 452 publications
(264 citation statements)
references
References 17 publications
18
238
1
7
Order By: Relevance
“…The germ-line mutations in these families have been described previously (Gayther et al, 1995(Gayther et al, , 1997. To control for a potentially biasing e ect of grade, a series of sporadic grade 3 breast tumours, previously characterized by the Breast Cancer Linkage Consortium (1997), was analysed in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…The germ-line mutations in these families have been described previously (Gayther et al, 1995(Gayther et al, , 1997. To control for a potentially biasing e ect of grade, a series of sporadic grade 3 breast tumours, previously characterized by the Breast Cancer Linkage Consortium (1997), was analysed in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Germ-line alterations of BRCA1 are more frequently localized in the 3' one-third of the gene (Gayther et al, 1995) and only one case of alteration at the exons 6 and 8 has been reported (The Breast Cancer Information Core). Therefore, in order to amplify BRCA1 transcripts in a large panel of samples, primers were chosen in these two di erent exons together with a chimeric RNA derived from the same sequence but containing an insert of 48 bp, which was used as a competitor (Ribieras et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of ovarian cancer is increased by 1.9 times for mutations within this region and the risk of breast cancer appears to be decreased (Thompson and Easton, 2001). Among BRCA1 mutation carriers, the relative proportion of ovarian cancer compared with breast cancer seems to be greater for mutations within the 5 0 two-thirds of the gene (Gayther et al, 1995). Allelic variation can explain differences in penetrance among families and among countries.…”
Section: Introductionmentioning
confidence: 99%